Analisis Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Mobil Honda BRV di Dealer Honda Abadi Cibiru dengan Metode Analitical Hierarchy Process dan Statistik: ANALISIS KEPUTUSAN PEMBELIAN MOBIL HONDA BR-V DI DEALER HONDA ABADI CIBIRU - Rismayani Deri, Rahmi; Rafika Ratik Srimurni; Ega Triyandi Permana (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The Honda Abadi Cibiru Car Dealer was unable to achieve the sales target of the Honda BRV. This causes various problems at the dealer. Therefore, research needs to be done to overcome it. This research aims to determine the effect of product quality, price and promotion on purchasing decisions statistically analysis (F-test and t-test). The methods used are AHP and statistics. Based on the AHP data processing of the five alternatives that have a big influence on the decision to purchase a Honda BRV car are price and promotion. Based on the results of respondents to product quality, price, promotion, and purchasing decisions are high. Simultaneously the results of the F test state that the variables of product quality, price and promotion have an effect on purchasing decisions. The results of the partial test (T test), the quality of the product does not have a real influence on purchasing decisions. The price variable has a real influence on the Purchase Decision. The promotion variable has an influence on purchasing decisions. For further researchers to add other variables that can affect purchasing decisions.